An Exploration into the Barriers Faced by Parents in Accessing Mental Health Services for their Children. - Quinn, Roisin (Marino Institute of Education, 2020)
This study explores the barriers faced by parents in accessing mental health services for children from the perspective of mental health care professionals. The research took a qualitative approach using semi-structured interviews with seven mental health care professionals. Data was analysed thematically. Parental fear of being judged as a failure, fear of being seen attending services and the prospect of a child being labelled with a diagnosis were identified as key deterrents. Systemic issues which were highlighted as significant barriers included deficiencies in the referral process and inadequate communication between services. Resource issues were also flagged as hindrances to parents accessing mental health services for their children. The findings point to the ongoing need for investment in community-based psychology services and the need to explore alternative avenues for service delivery online or by phone. Efforts to improve the referral process and mental health education and awareness remain key elements in increasing uptake of mental health services for children.
Keywords: Research Subject Categories